2014
DOI: 10.1210/er.2014-1045
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Decidualization of the Human Endometrium in Reproductive Health and Failure

Abstract: Decidualization denotes the transformation of endometrial stromal fibroblasts into specialized secretory decidual cells that provide a nutritive and immunoprivileged matrix essential for embryo implantation and placental development. In contrast to most mammals, decidualization of the human endometrium does not require embryo implantation. Instead, this process is driven by the postovulatory rise in progesterone levels and increasing local cAMP production. In response to falling progesterone levels, spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
975
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 860 publications
(988 citation statements)
references
References 625 publications
7
975
2
4
Order By: Relevance
“…As decidualization progresses, Notch1 is down-regulated (10,11), and this down-regulation is necessary to permit differentiation into the decidual phenotype, which was shown in a previous study (11) and is also shown in this study. Decidualization is dependent on cAMP stimulation, sustained PKA activity, and cAMP response elementbinding protein (CREB) activation (38,39), and N1ICD sequesters nuclear CREB and inhibits cAMP/PKA-mediated signaling (40). When N1ICD is overexpressed, cAMP/PKA-mediated signaling is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…As decidualization progresses, Notch1 is down-regulated (10,11), and this down-regulation is necessary to permit differentiation into the decidual phenotype, which was shown in a previous study (11) and is also shown in this study. Decidualization is dependent on cAMP stimulation, sustained PKA activity, and cAMP response elementbinding protein (CREB) activation (38,39), and N1ICD sequesters nuclear CREB and inhibits cAMP/PKA-mediated signaling (40). When N1ICD is overexpressed, cAMP/PKA-mediated signaling is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Decidualisation is the differentiation and proliferation of ESC that is initiated in the secretory phase of the menstrual cycle in response to rising levels of progesterone (reviewed in (Gellersen & Brosens 2014)). Decidualisation is accompanied by increased angiogenesis and leukocyte infiltration (Plaisier 2011) and is unique to species that undergo haemochorial placentation (Vogiagis & Salamonsen 1999).…”
Section: Decidualisationmentioning
confidence: 99%
“…Stabilized b-catenin induces endometrial glandular hyperplasia and formation, whereas aberrant activation of b-catenin leads to squamous cell metaplasia of the luminal epithelium, uncovering that b-catenin signaling is linked to normal uterine function as well as in tumorigenesis [67]. Conditional deletion of b-catenin in embryonic Müllerian duct mesenchyme resulted in FRT developmental abnormalities: underdeveloped oviducts in the knock-out embryo, stunted FRT development at birth with a decrease in proliferation in the mesenchyme and epithelium, as well as fewer uterine glands and a dramatic defect in the smooth muscle of uterine myometrium in adulthood [68,69]. The similar phenotypes of uncoiled oviducts between Wnt7a knock-out mice and b-catenin mutants raised the possibility that Wnt7a might mediate oviduct coiling in the anterior Müllerian duct through bcatenin-dependent signaling [69].…”
Section: Wnt Signaling In Uterine Developmentmentioning
confidence: 99%
“…Conditional deletion of b-catenin in embryonic Müllerian duct mesenchyme resulted in FRT developmental abnormalities: underdeveloped oviducts in the knock-out embryo, stunted FRT development at birth with a decrease in proliferation in the mesenchyme and epithelium, as well as fewer uterine glands and a dramatic defect in the smooth muscle of uterine myometrium in adulthood [68,69]. The similar phenotypes of uncoiled oviducts between Wnt7a knock-out mice and b-catenin mutants raised the possibility that Wnt7a might mediate oviduct coiling in the anterior Müllerian duct through bcatenin-dependent signaling [69]. Mice with conditional ablation of b-catenin in uteri suffered uterine developmental defects including a reduced overall weight and an impaired glandular formation [67].…”
Section: Wnt Signaling In Uterine Developmentmentioning
confidence: 99%
See 1 more Smart Citation